1980
DOI: 10.1002/bjs.1800670908
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of skin closure using continuous and interrupted nylon sutures

Abstract: Skin closure using continuous nylon sutures was compared with closure using interrupted nylon sutures in 105 consecutive patients undergoing laparotomy. Particular note was made of wound healing and wound infection. The incidence of wound infection was similar (3.9 per cent and 3.7 per cent respectively) and all wounds healed satisfactorily. The continuous method was quicker and cheaper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In our study, standard techniques of wound closure were followed in all the cases but no association was found with the type of closure similar to the study by McLean NR et al who found the similar incidence of wound infection with continuous or interrupted sutures. 15 Kore S et al did comparison of closure of subcutaneous tissue versus non-closure in relation to wound disruption after abdominal hysterectomy in obese patients and concluded that closure of the subcutaneous tissue after abdominal hysterectomy of women with at least 2.5 cms of subcutaneous tissue lowers the overall rate of complications leading to disruption of the incision. 16 Haddad V et al studied abdominal wound dehiscence and evisceration and the contributing factors so as to improve mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, standard techniques of wound closure were followed in all the cases but no association was found with the type of closure similar to the study by McLean NR et al who found the similar incidence of wound infection with continuous or interrupted sutures. 15 Kore S et al did comparison of closure of subcutaneous tissue versus non-closure in relation to wound disruption after abdominal hysterectomy in obese patients and concluded that closure of the subcutaneous tissue after abdominal hysterectomy of women with at least 2.5 cms of subcutaneous tissue lowers the overall rate of complications leading to disruption of the incision. 16 Haddad V et al studied abdominal wound dehiscence and evisceration and the contributing factors so as to improve mortality.…”
Section: Discussionmentioning
confidence: 99%
“…If the latter situation is desired, one can still tie the end of the suture to a remaining loop to prevent the unraveling of the entire suture. Other theoretical disadvantages, which include an increased frequency of wound infections or a decreased final tensile strength, have not yet been proven in animal studies or actual clinical situations 30,31 . Because of the economy of time and good results obtained with the running continuous suture, this technique can be valuable in many circumstances.…”
Section: Common Suturing Techniquesmentioning
confidence: 99%
“…The interrupted suture takes longer to perform than a running continuous suture and is prone to causing “railroad track” scars on cutaneous surfaces (Figure 9). 31 An advantage to interrupted sutures is that more selective adjustments of wound edges can be made than in a running continuous suture when buried sutures have inadequately evened out the wound edges. The procedure involves using a needle to enter or exit the skin on the high side more superficially and exit or enter the skin on the low side more deeply.…”
Section: Common Suturing Techniquesmentioning
confidence: 99%
“…Mclean et al compared interrupted and continuous nylon skin sutures (not subcuticular skin sutures) in 105 laparotomy wounds to evaluate wound healing and wound infection. 22 The incidences of wound infection were similar (3.7% and 3.9%, respectively), and all wounds healed satisfactorily.…”
Section: Discussionmentioning
confidence: 77%